Collective Cell Migration: "All for One and One for All". (December 2014) - Gupta, Tripti; Giangrande, Angela
Abstract Cell migration is a key mechanism during neural development, as it allows cells to reach their final destination from their birthplace. In some cases, cells migrate in isolation, whereas in others they migrate in collectives, as chains, streams, clusters, or sheets. The coordinated and timely process of collective migration eventually ensures the proper organization of the nervous system and its misregulation leads to severe diseases, including neurological disorders. This review impinges upon the cellular and molecular interactions underlying collective cell migration in animal models, and highlights the recent advances made through in vivo analyses of the Drosophila wing glia.